Analysis of the Ministry of the Environment’s Waste Database as a Source of Knowledge on Waste – A Case Study - Kowalski, Jakub; Krzos, Grzegorz (Analiza Bazy Danych Odpadowych Ministerstwa Środowiska jako źródła wiedzy o odpadach – studium przypadku, 2023)
Aim: The purpose of this study was to assess the usefulness and adequacy of the National Waste Database of the Ministry of the Environment (BDO) as the main source of information on waste in Poland. A representative sample of entities registered in the database was analysed in terms of responses to contact attempts and declarations concerning the sale of specific waste groups relevant to a planned investment by company X (company name withheld). Methodology: The survey was conducted using two main research methods: CATI and in-depth interview. The CATI method involved telephone contact with a representative sample of entities from the Waste Database to explore responses to contact attempts and declarations of sales of selected waste groups. The in-depth interview focused on detailed interviews with selected bidders who declared their willingness to cooperate in the supply of waste according to the research criteria. Results: The survey showed that out of a representative sample of 148 entities registered in the National Waste Database of the Ministry of the Environment, only 65.54% responded to the attempted contact using the CATI method. Of these responses, only 3.37% of entities declared an actual willingness to sell specific groups of waste. The in-depth interview method confirmed the willingness to cooperate with three of the five companies that declared a supply of waste. The conclusions of the survey highlight the incompleteness and the need to update data in BDO, which can lead to inefficient waste management and negative environmental and public health impacts. Implications and recommendations: The results of the study indicate significant implications for waste management in Poland. Incomplete and insufficiently updated data in the National Waste Database of the Ministry of Environment may lead to inefficient waste management and adverse consequences for the environment and public health. It is recommended that further research be carried out to further analyse the reliability of the data contained in the BDO and its timeliness. It is also worth considering measures to increase the transparency and availability of information in the database, which would contribute to more effective waste management in Poland. Educating BDO users on the proper use of data and encouraging cooperation of all stakeholders may also contribute to building a more reliable picture of the waste management situation. Originality/value: The originality and value of the research conducted derives from the analysis of the usefulness of the National Waste Database of the Ministry of the Environment as the main source of information on waste in Poland. The study used innovative methodological approaches such as CATI and in-depth interview to assess the reliability of the data and the adequacy of the information available in the database. In the context of waste management in Poland, our results highlight significant shortcomings in data updating and the need to increase transparency in waste management. The implications of our research point to the need for further efforts to improve data quality and availability, which can contribute to more efficient and sustainable waste management at the national level.
Business Informatics = Informatyka Ekonomiczna, 2023, Nr 1-2 (65-66), s. 23-32
Keywords: waste management; National Waste Database; efficiency of waste management; transparency of information; gospodarka odpadami; Ogólnopolska Baza Danych Odpadowych; efektywność zarządzania odpadami; transparentność informacji